2006
DOI: 10.1111/j.1443-1661.2006.00590.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Bacterial Identification by Colorectal Tissue Culture and Fluid Culture After Colonoscopic Washing

Abstract: Background: Inflammation of the colon is often found during colonoscopy. In order to confirm the pathogenesis of the lesion, bacterial cultures are applied. Biopsied tissue specimens are used for bacterial culture, and fluid culture after colonoscopic washing also has been used for bacterial identification. In the latter method, sterile saline solution is sprayed over the area and then is collected with the fluid. The two methods have not been compared with each other. Methods: The subjects comprised 89 cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…We demonstrated that endoscopy is more effective than standard stool collection, especially for diagnosing C jejuni and TB. Suda et al 19 reported a bacterial pathogen detection rate of 83.9% by intestinal fluid culture and 70.9% by tissue culture. Matsumoto et al 18 reported that biopsy specimens were more sensitive than fecal samples to culture (50% vs 20%).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We demonstrated that endoscopy is more effective than standard stool collection, especially for diagnosing C jejuni and TB. Suda et al 19 reported a bacterial pathogen detection rate of 83.9% by intestinal fluid culture and 70.9% by tissue culture. Matsumoto et al 18 reported that biopsy specimens were more sensitive than fecal samples to culture (50% vs 20%).…”
Section: Discussionmentioning
confidence: 98%
“…14,15 Endoscopy is acceptable when GI symptoms persist or worsen, 16 because it enables not only direct visualization but also sample collection during aspiration of intestinal fluid or biopsy. [17][18][19] Having a knowledge of specific visual endoscopic findings of colonic disease may prompt appropriate sample collection methods (biopsy or aspiration) or the use of suitable pathogen detection methods (microscopy, histology, culture, and polymerase chain reaction [PCR]), which can provide clues toward a definite diagnosis. However, few studies have reported on the gross appearance of infectious colitis, [5][6][7][8]12,13 and no objective criteria that are based on endoscopic findings exist.…”
mentioning
confidence: 99%
“…Endoscopy is not only useful for obtaining an image, but it is also useful for biopsy and aspiration of intestinal fluid 5 . We believe that endoscopic examination should be carried out even if the standard stool culture tests negative, especially in HIV patients who have symptoms of diarrhea.…”
mentioning
confidence: 99%